(untitled) (Journal of Educational Sciences, 2024)
The present article is devoted to the actual problem of using multimedia technologies in education, as well as investigating their effectiveness for engaging young teachers in innovative activities. The purpose of this study was to determine the effectiveness of an online course using edweb.net materials to engage young teachers in innovative activities. The study involved 60 young teachers divided into experimental and control groups of 30 participants each. The intervention consisted of providing the participants with 8 webinars covering different aspects of online teaching and learning using different tools and strategies followed by assignments. Adapted questionnaires were used to measure participants’ student-centeredness and propensity to incorporate new ideas and practices into their teaching. Additionally, some participants were interviewed for qualitative analysis. According to the results, in the experimental group, the average total score of innovativeness significantly increased during the research period compared to the control group (p = 0.043). Additionally, the experimental group exhibited a greater degree of student-centeredness at the post-test compared to the control group (p = 0.014). The interview findings further revealed favorable changes in the cybersecurity awareness of respondents from the experimental group, as well as their understanding of the importance of integrating digital resources in learning processes, compliance with ethical standards when using educational technology, as well as the desire for self-reflection and professional growth. The results of the study expand the understanding of the effectiveness of multimedia technologies in education and their impact on the professional development of young teachers. The conclusion contains a number of findings and suggestions on the importance of promoting and maintaining access to online courses and multimedia resources for young teachers, encouraging them to participate in online courses with active use of multimedia technologies, to exchange experiences and cooperate with colleagues to stimulate professional development and innovation, as well as the importance of continuing further research in the area. Keywords: innovation, student-centeredness, young teacher, online course, webinar.